054 Transforming Evidence From Multiple Guidelines Into User Friendly Clinical Practice Tools For Remote Cancer Treatment-Related Symptom Management: The Costars Project. (15th August 2013) - Stacey, D; Carley, M; Harrison, M
Abstract : Objectives: To transform evidence from guidelines for clinical practice tools for remote management of patients experiencing symptoms related to cancer treatment. Clinical practice protocols are defined as user-friendly knowledge translation tools to support patient care. These tools narrow the know-do gap by presenting the best available evidence from guidelines while using a format that is sensitive to how nurses think and what nurses do. Methods: Mixed methods descriptive study guided by CAN-IMPLEMENT©. The process involved: a) conducting a systematic search for guidelines; b) developing symptom-specific protocols using evidence from quality appraised clinical practice guidelines; c) reaching consensus on the clinical practice protocol template, and d) validating the clinical practice protocols. Results: Clinical practice protocols were developed and validated for 13 symptoms using 42 clinical practice guidelines with a median of 3 guidelines per protocol (range 1 for bleeding to 7 vomiting). For the first two protocols, source guideline AGREE rigour subscale ratings ranged from 8% to 86% (median 60.1; diarrhoea; 40.5 fever). The protocols were developed using guidelines, symptom severity questions included the Edmonton Symptom Assessment System, and iterative feedback from practicing nurses. Usability testing revealed: high readability, just the right amount of information, and appropriate terms. Access to protocols needs to be tailored to individual practices (e.g. electronic application, access to paper-based versions). Nurses requested training and support to implement them. Discussion: These tools, created from guidelines, transform evidence into user-friendly protocols for use by nurses when guiding patients at home to better manage their cancer treatment-related symptoms.